2008
DOI: 10.1089/jir.2007.0117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Expression, and Characterization of Chicken IFN -λ

Abstract: Interferons (IFN) provide a critical first line of defense against viral infection in vertebrates. Moreover, IFN-lambda, a recently identified group of mammalian IFN, has demonstrated antiviral potential in the treatment of mammalian viruses. With the growing concern over such diseases as avian influenza (AI), there is a pressing need for new antiviral strategies to manage problem viruses in poultry. Furthermore, the use of immune molecules, such as IFN-lambda, provides an attractive option for treating poultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…In contrast, chIFN-had only very mild inhibitory effects on these viruses (Fig. 1), in agreement with previous observations of other groups (17).…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, chIFN-had only very mild inhibitory effects on these viruses (Fig. 1), in agreement with previous observations of other groups (17).…”
Section: Methodssupporting
confidence: 93%
“…In addition to the type I IFNs, a single gene for chicken IFN-(chIFN-) has been described, and its product was shown to trigger a moderate antiviral response in the chicken macrophage cell line HD11 and in primary chicken embryonic fibroblasts (CEF) (17). A more recent report indicated that stimulation of CEFs with recombinant chIFN-induces ISGs in a temporal pattern distinct from that of type I IFNs (18).…”
mentioning
confidence: 99%
“…In contrast, human keratinocytes and hepatocytes, which expressed soluble IFNLR1 mRNA at much lower levels compared with PBMCs, responded to IFN-λ1. A previous report revealed that chicken IFN-β could induce a significant increase in the mRNA expression of an ISG, TLR3, in chicken splenic mononuclear cells [12]. Soluble IFNLR1 may possibly inhibit the response to IFN-λ in certain cell types in chickens.…”
Section: Discussionmentioning
confidence: 96%
“…A type III IFN, IFN-λ was recently identified in vertebrates. In birds, chicken IFN-λ was cloned previously, and its antiviral activity was reported [12]. However, most of the biological properties of chicken IFN-λ has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation